The Implementation of Grammar Translation Method (GTM) and Communicative Language Teaching (CLT) in Teaching Integrated English - Hari Prastyo (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2015)
Fluency and accuracy are the target of learning English. Both of them have important role for the students who learn English. Consequently, a teacher should consider fluency and accuracy of the English used by the students in the classroom. It means that teaching English should teach both linguistics and communicative competence. To teach lingusitics competence, a teacher can use Grammar Translation Method (GTM). Furthermore, a teacher needs Communicative Language Teaching (CLT) Method to teach commuicative competence. This article will study about the “The Implementation of Grammar Translation Method (GTM) and Comunicative Language Teaching (CLT) Method in Teaching Integrated English” which are applied in Basic English Station (BEST) Course of Jombang. This English course can combine both GTM and CLT to teach the students. For the first time, the writer will discuss about GTM and CLT theory. Then he will describe the programs and the materials applied in this course. Afterward, the writer will discuss about the implementation of GTM and CLT which are used to explain the materials and how GTM and CLT are applied in the programs that this course has. It means that, GTM and CLT will be applied both in the classroom and the programs of this English course